Morphological and phylogenetic analyses reveal two new species of Tubeufia (Tubeufiales, Tubeufiaceae) from freshwater habitats in China - Xiao-Yan Ma; Fu Tian; Jiang-Fen Feng; Min-Min Wang; Huan-Huan Shi; Jian Ma (MycoKeys)
Tubeufia is a genus of helicosporous hyphomycetes distinguished by a high degree of morphological variation in its asexual morphs. During an investigation of helicosporous fungi in tropical regions, four fungal strains were isolated from submerged decaying wood in Hainan Province, southern China. Multigene phylogenetic analyses based on a combined ITS–LSU–tef1-α–rpb2 sequence dataset were conducted to determine the phylogenetic placement of the four fungal strains, which showed two distinct new species. Morphological characteristics were also used to support their taxonomic delimitation in addition to the molecular phylogeny. Two novel species, Tubeufia yanuodaensis and T. yinggelingensis, are described and illustrated.